2007
DOI: 10.11120/ened.2007.02010023
|View full text |Cite
|
Sign up to set email alerts
|

Engineering more engineers — bridging the mathematics and careers advice gap

Abstract: The popularity of engineering degrees among undergraduates is in decline. There are many barriers affecting the supply of engineering undergraduates and the School of Technology at the University of Glamorgan has identified lack of awareness of what engineering entails and lack of mathematical preparedness as two principal barriers to potential students studying engineering in higher education. To show how the School of Technology overcame these barriers, the role of the Network75 Recruitment and SupportOffice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…The second factor contributing to Mexican‐origin students' disparate STEM pursuit may be the quality and adequacy of career advice they receive during high school (Eleri et al, 2007). STEM research emphasizes the importance of career advising for students' STEM pursuits because career aspirations center on real occupations to which they have at least some exposure (Miller, 1999; Riegle‐Crumb et al, 2011; Stipanovic & Woo, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The second factor contributing to Mexican‐origin students' disparate STEM pursuit may be the quality and adequacy of career advice they receive during high school (Eleri et al, 2007). STEM research emphasizes the importance of career advising for students' STEM pursuits because career aspirations center on real occupations to which they have at least some exposure (Miller, 1999; Riegle‐Crumb et al, 2011; Stipanovic & Woo, 2017).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The neighborhood labor market context (e.g., general condition and types of industry clusters) can be viewed as an institutional resource to the extent that it provides job opportunities that delineate the local opportunity structure (Bozick, 2009; Engberg & Gilbert, 2014). Numerous studies document that often times, STEM minority students receive little or no advice about the engineering or high‐tech profession at school context, and, in turn, do not study relevant subjects for entry into many STEM‐related careers (Eleri et al, 2007; Navarro et al, 2007). Other research on students from economically disadvantaged backgrounds suggests the educational paths of Mexican‐origin students may be particularly sensitive to job availability within the local workforce, as opposed to school counseling (Bozick, 2009; Chiquiar & Salcedo, 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Međutim, to nije dobiveno za interese za zanimanja u domeni inženjerstva i tehnologije, što implicira da učenici ne ostvaruju jasnu poveznicu između gradiva koje uče u STEM školskim predmetima i sadržaja ovih zanimanja. Istraživanja uistinu potvrđuju da učenici nemaju dovoljno znanja o sadržaju STEM zanimanja, posebice u inženjerstvu (Eleri, Prior, Lloyd, Thomas i Newman-Ford, 2007). Zato roditelji koji su inženjeri ili tehnolozi mogu imati istaknutu ulogu modela i informatora upravo za karijere na tom području i tako pozitivno utjecati na učeničke interese.…”
Section: Značenje Roditeljskoga Stem Zanimanjaunclassified
“…This has tremendous implications for engineering programs because students, as well as the general public, typically have limited views of the engineering profession. Studies have shown that middle school and high school students have a narrow perspective of what engineers do, limited for example to mechanics, maintenance workers, and construction workers (English, Hudson, Dawes, 2011;Bowen, Prior, Lloyd, Thomas, & Newman-Ford, 2007;Knight & Cunningham, 2004), and are not aware of the contributions that engineers can make to solve global challenges and the impact they can have in society. When students are exposed to advanced engineering topics and application coursework, their understanding of the widerange of careers that engineers expands, and their interest in an engineering profession increases (Fantz, Siller, & DeMiranda, 2011;Oware, Capobianco, & Diefes-Dux, 2007).…”
Section: Introductionmentioning
confidence: 99%